Capacity Building of Posyandu Cadres in Monitoring Toddler Growth in the Working Area of Puuwatu Health Center, Kendari City - Rosnah; Teguh Fathurrahman; Imanuddin; Sitti Rachmi Misbah; Nurjannah; Syaifudin Suhri Kasim (Indonesian Journal of Community Services, 2023)
Monitoring the growth of toddlers at the Posyandu is an activity to detect early the emergence of nutritional problems in toddlers. Posyandu is the center of community activities in health care and family planning efforts to meet health needs and improve the nutritional status of the community. Improper anthropometric measurements in toddlers can lead to misclassification of nutritional status and loss of important interventions. It takes Posyandu cadres who are trained and know the procedures for monitoring growth in toddlers. The purpose of this community service is to provide counseling and training on how to monitor toddler growth to Posyandu cadres in the working area of the Puuwatu Health Center, Kendari City. It was held on October 2023, at the Puuwatu Health Center hall, which was attended by 30 (thirty) Posyandu cadres. Conclusion: the knowledge and skills of cadres about anthropometric measurements in toddlers, how to fill out KMS books, and interpret the results of measuring the weight of toddlers have increased after counseling and practice. Suggestion: It is necessary to conduct training and mentoring activities for Posyandu cadres periodically, and the Puskesmas is expected to be able to monitor the work of Posyandu cadres by accompanying and providing education about monitoring toddler growth and correct anthropometric measurements.